Faktor Sosiodemografi yang Memengaruhi Pemilihan Metode Kontrasepsi - Asti Dewi Rahayu Fitrianingsih; Soenarnatalina Melaniani (Universitas Airlangga, 2016)
Long term contraception entered into government programs. Government suggested to use long term contraception effectively to postponing pregnancy, spacing of birth and terminating fertility. In fact, couples of reproductive ages in Indonesia were likely to still choose short-term contraceptive than long-term contraceptive. This research analyzed sosiodemografi factors that aff ecting the selection of contraception method in Gading Public Health Center Tambaksari Surabaya. This research used analytical study with case control design. Research population totaled 84 respondents. Sampling technique used simple random sampling and got 42 cases and 42 controls. The variables were sosiodemografi factors. Data were analyzed using that multivariate logistic regression with a level of signifi cance value α = 0,05. The results showed four signifi cant variables were age (p=0,018), education (p=0,024), occupation (p=0,008), parity (p=0,034), also status of women (p=0,002. Sosiodemografi factors such as age, occupation, parity and status women aff ect the injection contraceptive acceptors did not choose long acting contraception method in Tambaksari Surabaya Gading Public Health Center. The granting of complete information about all types of contraception is important so that the fertile age couples can choose contraception that suits their need.